BRM/SMARCA2 promotes the proliferation and chemoresistance of pancreatic cancer cells by targeting JAK2/STAT3 signaling. (28th August 2017) - Zhang, Zhengkui; Wang, Feng; Du, Chong; Guo, Huahu; Ma, Ling; Liu, Xiaoran; Kornmann, Marko; Tian, Xiaodong; Yang, Yinmo
Abstract: Background: BRM is one of two evolutionarily conserved catalytic ATPase subunits of SWI/SNF complexes and plays important role in cell proliferation, linage specification and development, cell adhesion, cytokine responses and DNA repair. BRM is often inactivated in various types of cancer indicating its indispensable roles in oncogenesis but the mechanisms remain poorly understood. Methods: BRM expression in clinical pancreatic cancer samples was examined by immunohistochemistry and the correlation with patient survival was analyzed. shRNAs targeting BRM were used to establish stable BRM knockdown BxPC-3 and T3M4 cell lines. Cell viability was assessed by CCK-8 assay. Cell proliferation was measured by EdU incorporation assay, colony formation assay and Ki67 staining. Cell cycle and apoptosis were examined by flow cytometry. Growth and chemosensitivity of xenografts initiating from BRM-deficient cells were evaluated, and in situ apoptosis was detected by TUNEL assay. The status of JAK-STAT3 signaling was examined by real-time PCR and Western blot analysis. Results: High BRM expression was correlated with worse survival of pancreatic cancer patients. BRM shRNA reduced the proliferation and increased the sensitivity of pancreatic cancer cells to gemcitabine in vivo and in vitro, and these effects are associated with the inhibition of STAT3 phosphorylation and reduced transcription of STAT3 target genes. Conclusion: We reveal a novel mechanism by which BRM could activate JAK2/STAT3 pathway to promote pancreatic cancer growth and chemoresistance. These findings may offer potential therapeutic targets for pancreatic cancer patients with excessive BRM expression. Highlights: BRM knockdown inhibits pancreatic cancer cell viability, proliferation and cell cycle progression. BRM knockdown inhibits pancreatic cancer cell xenograft in nude mice. BRM knockdown increases chemosensitivity of pancreatic cancer cells. BRM knockdown inhibits the activation of JAK2/STAT3 signaling.